2021
DOI: 10.3390/cancers13225765
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Neuroendocrine Prostatic Carcinoma

Abstract: Neuroendocrine prostate cancer (NEPC) is an aggressive subtype of prostate cancer that typically has a high metastatic potential and poor prognosis in comparison to the adenocarcinoma subtype. Although it can arise de novo, NEPC much more commonly occurs as a mechanism of treatment resistance during therapy for conventional prostatic adenocarcinoma, the latter is also termed as castration-resistant prostate cancer (CRPC). The incidence of NEPC increases after hormonal therapy and they represent a challenge, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…Despite the great impact and evolution that PSMA has had, there are clinical reports that suggest that PSMA-targeted imaging does not visualize NEPC tumours. Studies have demonstrated that AR regulate the expression of FOLH1, which is the gene responsible for encoding the transmembrane protein prostate-specific membrane antigen; also, the induction of lineage plasticity by AR inhibition leads to neuroendocrine differentiation and PSMA suppression [ 22 , 23 ]. In our study 18 F–PSMA–1007 PET/ CT detected a significant number of lesions, especially bone metastases, with an even better detection rate than 18 F–FDG PET/ CT at these specific sites, which could be possibly explained by the identification of mixed histologic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great impact and evolution that PSMA has had, there are clinical reports that suggest that PSMA-targeted imaging does not visualize NEPC tumours. Studies have demonstrated that AR regulate the expression of FOLH1, which is the gene responsible for encoding the transmembrane protein prostate-specific membrane antigen; also, the induction of lineage plasticity by AR inhibition leads to neuroendocrine differentiation and PSMA suppression [ 22 , 23 ]. In our study 18 F–PSMA–1007 PET/ CT detected a significant number of lesions, especially bone metastases, with an even better detection rate than 18 F–FDG PET/ CT at these specific sites, which could be possibly explained by the identification of mixed histologic subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The only role of CT is to show an irregularly enlarged prostate and for nodal staging. CT plays a primary role in metastatic staging for detection and restaging of bone and lung metastases in these cases ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…While mpMRI is now considered the technique of choice for initial and local (T) tumor staging, PET/CT and PET/MRI have shown great value in distant extraprostatic (N and M) staging. mpMRI can also differentiate prostatic carcinoid from the usual prostatic adenocarcinoma based on the considerably larger size and mild hyperintensity of the tumor on T2W images ( 18 ). Recently, biopsy guided by the fusion of MRI and transrectal ultrasound images (called MRI-TRUS fusion biopsy) is increasingly used where MRI findings are used as a reference for US-guided biopsy, allowing for increased accuracy and precision which is frequently done in our center and in this patient as well ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lethal disease with median survival of less than 1 year from the time of detection, neuroendocrine prostate cancer (NEPC) accounts for approximately 25% of all therapy- and castration-resistant prostate cancer (tCRPC) [ 1 , 2 ]. Since prostatic adenocarcinoma (ADPC) is a typical androgen-dependent (AD) cancer, androgen deprivation therapy is the standard of care for this disease.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several lines of studies have reported upregulated levels of SSTR2 expression in NEPC [ 30 ]. For instance, the expression level of SSTR2 was found to be elevated following hormone depletion therapy [ 22 ], and high uptake of 68 Ga-DOTATATE was observed in biochemically relapsed prostate cancer [ 1 , 31 ]. Most recently, targeting of SSTR2 was reported as a practical strategy to develop a polymeric nanoparticle system for NEPC therapy [ 32 ].…”
Section: Introductionmentioning
confidence: 99%